2018
DOI: 10.1016/j.virol.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus E6 interaction with cellular PDZ domain proteins modulates YAP nuclear localization

Abstract: HPV E6 oncoproteins associate with cellular PDZ proteins. In addition to previously identified cellular PDZ proteins, we found association of the HPV16 E6 PBM with the Dystrophin Glycoprotein Complex, LRCC1, and SLC9A3R2. HPV18 E6 had additional associations when lysates from adenomatous cell lines were used including LRPPRC, RLGAPB, EIF3A, SMC2 and 3, AMOT, AMOTL1, and ARHGEF1; some of these cellular PDZ proteins are implicated in the regulation of the YAP1 transcriptional co-activator. In keratinocytes, nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 76 publications
2
49
0
Order By: Relevance
“…Several studies have also showed that aberrant YAP accumulation in the nucleus of cancer cells was found in both cervical cancer and HPV-positive OSCC, and HPV-positive patients with higher YAP levels usually had a more advanced stage (54)(55)(56). Moreover, Webb Strickland and colleagues have reported that E6 oncoprotein could associate with cellular PDZ domain proteins to promote the nuclear localization of YAP (57). In our study, we put forward a pathway in which miR-550a-3-5p, down-regulated by E6 oncoprotein, inhibited YAP but not TAZ in HPV-positive OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also showed that aberrant YAP accumulation in the nucleus of cancer cells was found in both cervical cancer and HPV-positive OSCC, and HPV-positive patients with higher YAP levels usually had a more advanced stage (54)(55)(56). Moreover, Webb Strickland and colleagues have reported that E6 oncoprotein could associate with cellular PDZ domain proteins to promote the nuclear localization of YAP (57). In our study, we put forward a pathway in which miR-550a-3-5p, down-regulated by E6 oncoprotein, inhibited YAP but not TAZ in HPV-positive OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also showed that aberrant YAP accumulation in the nucleus of cancer cells was found in both cervical cancer and HPVpositive OSCC, and HPV-positive patients with higher YAP levels usually had a more advanced stage [60][61][62]. Moreover, Webb Strickland and colleagues have reported that E6 oncoprotein could associate with cellular PDZ domain proteins to promote the nuclear localization of YAP [63]. In our study, we put forward a pathway in which miR-550a-3-5p, downregulated by E6 oncoprotein, inhibited YAP but not TAZ in HPV-positive OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that E6 protein can promote YAP1/TAZ transnational activity by binding to the PDZ domain of TAZ [17]. We found that E6 level was positively related to SOX21-AS1.…”
Section: E6-associated Sox21-as1 Is Closely Related To the Expressionsupporting
confidence: 51%